An in-depth investigation of student information gathering meetings with stakeholders and domain experts - Loweth, Robert P.; Daly, Shanna R.; Hortop, Amy; Strehl, Elizabeth A.; Sienko, Kathleen H. (International journal of technology and design education, 2022)
Information gathering activities in engineering design projects play an important role in the identification and definition of stakeholder needs and requirements. However, few studies have explored how students gather information from stakeholders and domain experts in capstone design settings. In this study, we analyzed audio recordings from 19 information gathering meetings submitted by six capstone design teams to investigate how student designers gathered information during these meetings. Our findings include 22 information gathering behaviors that student design teams exhibited during their meetings, half of which were more similar to recommended best practices for information gathering and half of which were less similar. Our findings, including the list of behaviors and associated examples, may be used to guide student designers in employing effective information gathering approaches.